2005
DOI: 10.1016/j.bbabio.2005.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor studies on non-photochemical plastoquinone reduction and H2 photoproduction in Chlamydomonas reinhardtii

Abstract: In the absence of PSII, non-photochemical reduction of plastoquinones (PQs) occurs following NADH or NADPH addition in thylakoid membranes of the green alga Chlamydomonas reinhardtii. The nature of the enzyme involved in this reaction has been investigated in vitro by measuring chlorophyll fluorescence increase in anoxia and light-dependent O(2) uptake in the presence of methyl viologen. Based on the insensitivity of these reactions to rotenone, a type-I NADH dehydrogenase (NDH-1) inhibitor, and their sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
87
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(89 citation statements)
references
References 65 publications
2
87
0
Order By: Relevance
“…The absence of genes encoding subunits of the chloroplast NDH-1 complex was confirmed by the recent sequencing of the C. reinhardtii nuclear genome. Despite the absence of a plastidial NDH-1 complex, significant non-photochemical reduction of PQ has been reported in Chlamydomonas thylakoids (4,5,54). Moreover, both chlororespiration and cyclic electron flow activity around PSI have been reported in the algal species (6,7,55,56).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The absence of genes encoding subunits of the chloroplast NDH-1 complex was confirmed by the recent sequencing of the C. reinhardtii nuclear genome. Despite the absence of a plastidial NDH-1 complex, significant non-photochemical reduction of PQ has been reported in Chlamydomonas thylakoids (4,5,54). Moreover, both chlororespiration and cyclic electron flow activity around PSI have been reported in the algal species (6,7,55,56).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, both chlororespiration and cyclic electron flow activity around PSI have been reported in the algal species (6,7,55,56). Based on a pharmacological approach, Mus et al (5) concluded that a type II NAD(P)H dehydrogenase would be involved in the NAD(P)H-dependent non-photochemical reduction of PQ in C. reinhardtii thylakoids. In bacterial species lacking NDH-1, type II dehydrogenases have been reported to sustain respiratory activity by allowing NADH turnover (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the PGR5/PGRL1 pathway and the NDH complex have the ability to reduce plastoquinone (PQ) by using ferredoxin as the electron donor (6). A similar activity exists in the green alga Chlamydomonas reinhardtii, but this organism does not encode the subunits of the NDH complex (7)(8)(9). Instead, a monomeric type II NAD(P)H:quinone oxidoreductase, NDA2, takes over the function of the NDH complex in cyclic electron flow and chlororespiration (10,11).…”
mentioning
confidence: 99%